Are illness perceptions related to future healthcare expenditure in patients with somatoform disorders?. Issue 13 (October 2014) - Frostholm, L.; Petrie, K. J.; Ørnbøl, E.; Fink, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Somatoform disorders are costly for society in terms of increased healthcare expenditure. Patients' illness perceptions have been found to play a role in somatoform disorders. However, it is unclear whether illness perceptions predict higher health costs in these patients. Method A total of 1785 primary care patients presenting a new health complaint completed a questionnaire on their illness perceptions and emotional distress before the consultation. The physicians completed a questionnaire for each patient on diagnostics after the consultation. In a stratified subsample, physician interviewers established diagnoses of DSM-IV somatization and undifferentiated somatoform disorders (n = 144) using the Schedules for Clinical Assessment in Neuropsychiatry. Healthcare expenditure was obtained from Danish health registers for a 2-year follow-up period. Results Patients had more negative perceptions of their well-defined physical health problems when they had a co-morbid somatoform disorder. A strong illness identity [β = 0.120, 95% confidence interval (CI) 0.029–0.212, p = 0.012], perceived negative consequences (β = 0.010, 95% CI 0.001–0.019, p = 0.024), a long timeline perspective (β = 0.013, 95% CI 0.005–0.021, p = 0.001), low personal control (β = − 0.009, 95% CI –0.015 to −0.002, p = 0.011) and negative emotional representations (β = 0.009, 95% CI 0.002–0.017, p = 0.020) predicted healthcare expenditure in somatoform disorders. Conclusions The results suggest that illness perceptions play a role in the perpetuation of symptoms in somatoform disorders and predict higher future healthcare expenditure among a subgroup of these patients.